Factors related to health literacy among Brazilian adolescents: cross-sectional study - Pimentel, Sidiany Mendes; De Avila, Marla Andréia Garcia [UNESP]; De Medeiros, Vinnicius Dias Alves; Prata, Rafaela Aparecida [UNESP]; Nunes, Hélio Rubens De Carvalho [UNESP]; Da Silva, Juliana Bastoni (FapUNIFESP (SciELO), 2024)
Objective: To analyze the relationship between sociodemographic and clinical factors with health literacy in Brazilian adolescents. Method: This is a cross-sectional study with 526 adolescents aged 14 to 19. Data were collected virtually between July and September 2021 using a sociodemographic characterization questionnaire, clinical profile and the Health Literacy Assessment Tool - Portuguese version. The variables were evaluated by multiple linear regression with normal response, with significance p < 0.05. Results: The average age was 16.9 years (±1.6), the average health literacy score was 25.3 (±5.4). Female gender (p = 0.014), university educational level (p = 0.002) and use of medication (p = 0.020) were related to higher levels of health literacy. Adolescents with chronic illnesses had a higher total literacy score, on average 1.51 points, compared to those without chronic illnesses. Conclusion: Male adolescents and those with less education performed worse in health literacy and, therefore, deserve special attention in health promotion actions.
Factores relacionados con la alfabetización en salud de adolescentes brasileños: estudio transversal
Fatores relacionados ao letramento em saúde de adolescentes brasileiros: estudo transversal
Keywords: Adolescent Development; Adolescent Health; Alfabetización en Salud; Desarrollo del Adolescente; Desenvolvimento do Adolescente; Determinantes Sociais da Saúde; Determinantes Sociales de la Salud; Health Literacy; Health promotion; Letramento em Saúde; Promoción de la Salud; Promoção da Saúde; Salud del Adolescente; Saúde do Adolescente; Social Determinants of Health